Revisiting the relationship between essential tremor and Parkinson's disease - Fekete, R.; Jankovic, J. (Movement disorders, 2011)
Background: The relationship between essential tremor and Parkinson's disease has been a subject of reviews and debates for long time, but there is now growing evidence that the two common movement disorders are pathogenically related, at least in some patient populations. Methods: PubMed as well as authors' own files were searched for relevant keywords regarding overlap between the disorders in clinical features as well as on epidemiologic, genetic, imaging, and pathological studies. Results: New findings in each of these categories are critically reviewed and placed in the context of previously published data. DISCUSSION: Although we believe that there is compelling evidence for the notion that some patients with “pure” ET evolve into PD, the biologic nature of the association is not well understood. Furthermore, it is not clear what factors predict which ET patients later develop PD and whether patients with PD are more likely to develop ET. Further epidemiologic, clinical, genetic, imaging, and pathological studies are needed to better understand this mixed, ET‐PD phenotype. © 2011 Movement Disorder Society